Quality control of tablets from Solidarity Pharmacy Program of Maringá-PR (Research, Society and Development, 2022)
The Solidarity Pharmacy Program de Maringá-PR aims to increase access to medicines for the population, through the distribution of medicines donated by users. Interchangeability between generic and reference drugs becomes possible, as generics have the same properties as their reference. For such proof, quality control tests are carried out to verify the existence of pharmaceutical equivalence. The objective of this study was to perform quality control tests on tablets donated to the Program. Lamotrigine, Atorvastatin and Clomipramine Hydrochloride and the similar Viverdal® were used to perform the tests, in addition to the reference drug Citalor®, to evaluate its pharmaceutical equivalence with Atorvastatin, its generic. The tablets were subjected to tests for weight determination, hardness, disintegration, dissolution and microbiological control that are described in the Brazilian Pharmacopoeia (VI edition, 2019) and to the dosage test described in the United States Pharmacopoeia (2021e), with adaptations. The results obtained in the tests, for each drug, were in accordance with the specifications of their respective monographs. In addition, pharmaceutical equivalence between the generic drug and its reference Atorvastatin was proven. Thus, it is inferred that the analyzed drugs are suitable for use, ensuring quality, safety and efficacy of the treatment, in addition to allowing interchangeability between the generic and reference Atorvastatin, since they have pharmaceutical equivalence.